Peptide-induced permeation of model membranes by antimicrobial peptidomimetics - Carvalho, Carina Martins (2015)
In the present communication, a set of Peptaibolin and several peptidomimetics incorporating unnatural α,α-dialkylglycines (Deg, Dpg, Ac6c) were studied for their ability to interact and permeate model membranes from phosphatidylcholine/cholesterol, in different ratios. The permeation activity was monitored by fluorescence spectroscopy, following the release of encapsulated 6-carboxyfluorescein.